The Resilience of Transracial Korean American Adoptees: Cultural Identity Crisis within the Family and the Mediating Effects of Family Conflict and Cohesiveness during Adversity. Issue 3 (2nd July 2016) - Lee, Diane Sookyoung
ABSTRACT: This study used a mixed-methods approach to examine the family practices that are fundamental for fostering resilience among 34 transracially adopted Korean American youths living with White American parents in the United States. The results demonstrate that in addition to experiencing stress related to their education and occupation, Korean American adoptees may encounter cultural identity crises. The negative effects of life stress on adoptees' mental health, however, were diminished once family cohesiveness and conflict were taken into account. Study findings have important implications for various stakeholders who seek to cultivate a healthy living environment for society's children (i.e., orphans).